ANALISIS KARAKTER YANG DAPAT DITUMBUHKAN DALAM MATERI PEMBELAJARAN GEOGRAFIS INDONESIA DI SEKOLAH DASAR - Melia Nurkhalisa; Muthia Aprianti; Tin Rustini (STKIP Subang, 2023)
Nowadays, there are problems that show that there are still many students who have not implemented character values ​​in their daily lives. Where this cannot be denied is part of the impact of environmental changes which are currently increasingly heading in a global direction, so that elementary school students who are still in a position where they do not yet have a complete stance or in other words are still unstable, have their focus shifted towards other things. - things that actually lead to a decline in character values. Therefore, this research aims to analyze what character values ​​are contained in geography learning, especially material regarding the geographical conditions of Indonesia in grade 5 elementary schools. This research uses a library study method, where the data collection technique is by conducting a review of books, literature, notes, journals that are related to the problem being discussed